Art and life: poetic and educational processes in making in contemporary art - Silva, Geovanni Lima da (Farol, 2024)
The text presented here is the result of the conference "Exercises to remember: blackness and performance in the construction of self", held during the XV Capixaba Seminar on the Teaching of Art: Urgent Dialogues, at the Federal University of Espírito Santo, in August 2023. The text presents the aspects of the artistic residency "Exercises to remember" by myself and the artist Carla Borba, as well as the artistic works of Tribal Ycsander; Rafa Black; CS, aka myself; Patthy Oliver and Jaiara Dias, young participants of the Youth Reference Centers - CRJs, in the municipalities of Vila Velha, Serra and Cariacica and Linhares and Colatina in Espírito Santo.
Keywords: Art; Art Education; Youths; Urgent Dialogues